Regulations on the practice of aesthetic medicine: a comparative study between Malaysia and the United Kingdom / Sarah Amani Lee Shamir Lee …[et al.] - Shamir Lee, Sarah Amani Lee; Abdul Mua'en, Syahira Farhani; Zulkhefli, Wan Zakiah; Rosabell, Marcella; Zakaria, Sakinah (2014)
This project paper is basically discussing on the issues regarding the aesthetic practice in Malaysia and some comparisons are made with that of the United Kingdom. Apart from that, this research paper further explains on the origin and the history of aesthetic medicine. Besides, the requirements of a good aesthetic practitioner are also highlighted in this project paper. The Guideline on Aesthetic Medical Practice for Registered Medical Practitioners 2013 then came into existence to govern the conduct of aesthetic practitioners in Malaysia. This guideline is prepared by a task force formed by the Ministry of Health together with the relevant professional bodies. There is a need for this guideline because aesthetic medical practice is not a medical specialty but an area of interest in the medial practice. The guidelines define the scope of practice allowed, minimum level of competency required and the process of registration for medical practitioners. However, when this Guideline is compared with the Standard Care Act 2000 which is established in United Kingdom, a few defects of the Guidelines could be seen throughout. The legal responsibilities of the practices, given the technical demands of the treatment offered, have resulted in the need for exclusive specialization in the field of aesthetic medicine. For that, a few recommendations have been proposed so that the practice of aesthetic medicine in our country could be enhanced and therefore provide more protection for people who seek aesthetic treatment.